From absences to emergences: Foregrounding traditional and Indigenous climate change adaptation knowledges and practices from Fiji, Vietnam and the Philippines - See J; Cuaton GP; Placino P; Vunibola S; Thi HD; Dombroski K; McKinnon K (Elsevier B.V., 2024)
The differential impacts of climate change have highlighted the need to implement fit-for-purpose interventions that are reflective of the needs of vulnerable communities. However, adaptation projects tend to favour technocratic, market-driven, and Eurocentric approaches that inadvertently disregard the place-based and contextual adaptation strategies of many communities in the Global South. The paper aims to decolonise climate change adaptation guided by the critical tenets of ‘Decolonising Climate Adaptation Scholarship’ (DCAS). It presents empirical case studies from Fiji, Vietnam, and the Philippines and reveals the different ways that Indigenous and local knowledge (ILK) and strategies are devalued and suppressed by modernist and developmentalist approaches to climate adaptation. The paper then foregrounds some of the adaptive techniques that resist and remain, or have been re-worked in hybrid ways with ILK. Ultimately, this paper combats the delegitimisation of ILK by mainstream climate change adaptation scholarship and highlights the need for awareness and openness to other forms of knowing and being.